Penerapan Teknik Koreksi Warna pada Rekaman High Dynamic Range Film Dokumenter Di Balik Seragam Biru - Zhahirin, Muhamad Nujjiya; Komariah, Kokom; Mahameruaji, Jimi Narotama (Jurnal Ilmiah Multimedia dan Komunikasi, 2024)
The documentary film â€œDi Balik Seragam Biruâ€ was created using the HDR format, in which it produces realistic images with a wider color gamut. This process presents unique visual challenges, particularly in color correction, since changes in shooting conditions can affect visual consistency. This study aims to apply color correction techniques to address inconsistencies in HDR footage. The study provides academic benefits by developing color correction methods for the HDR format, which can serve as an important reference for researchers exploring similar techniques in film and television production. Practically, the workflow and techniques used offer actionable guidance for practitioners to ensure consistent visual quality and to provide an optimal viewing experience for the audience. The creation process includes color management, the application of the scene-referred concept, and color correction techniques such as normalization, balancing, and shot matching. The findings of the study show that color management in modern cameras allows for recording image data with greater detail. The scene-referred workflow provides better control in achieving the desired visual outcome. Color correction techniques play an essential role in ensuring visual uniformity and consistency. Normalization helps standardize brightness levels across shots, while the balancing technique ensures color stability throughout the film. Shot matching aligns colors and contrast, ensuring smooth transitions between shots without visual disruptions.